Neat and clean - Aydin, H.; Nestelbacher, R.; Joubert, I.A.; Geppert, M.; Himly, M. (Open Schools Journal for Open Science, 2020)
Surfactants are a common component of many cleaning products and detergents. However, the production of these surfactants often requires the use of petroleum. In nature we can find plants, such as the lotus flower, whise leaves have developer a self-cleaning mechanism. Due to nano-sized hyedrophobic wax nubs on the surface of the leaf, water droplets have only a very samll contact area. The water’s surface tension subsequently leads to the droplet rolling off the leaf, taking dirt partcles with it.